2020
DOI: 10.3390/met10101279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Double Pulse Resistance Spot Welding Process on 15B22 Hot Stamped Boron Steel

Abstract: Double pulse resistance spot welding process by applying a second step welding current is a new pathway to alter the mechanical properties for advanced high strength steels. Herein, the resistance spot welding (RSW) of hot stamped boron steel 15B22 by one-step and two-step welding with different welding currents is investigated. The results of the tensile–shear test, size of the weld nugget, hardness distribution, microstructure, and failure mode of different welding parameters are analyzed. The weldment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…This indicates that a certain amount of heat is retained in the weldment at the end of cooling, which supplements the total heat input. Aghajani et al [21] and Lee et al [33] reported similar observations that the FZ size increases using double pulse RSW.…”
Section: Enlargement Of Fzmentioning
confidence: 66%
See 3 more Smart Citations
“…This indicates that a certain amount of heat is retained in the weldment at the end of cooling, which supplements the total heat input. Aghajani et al [21] and Lee et al [33] reported similar observations that the FZ size increases using double pulse RSW.…”
Section: Enlargement Of Fzmentioning
confidence: 66%
“…It can be observed that welds (i.e., SPW, sample 1, sample 2, sample 3, sample 4, sample 5, sample 6, sample 9 and sample 13) failed in the IF mode, while other welds failed in the PF/PIF/PTPP modes. Lee et al [ 33 ] also reported that double-pulse RSW results in higher heat input, which in turn affects the weld size, microstructure of the HAZ and failure mode. Increasing heat input during the second pulse intensifies the martensite tempering both in the FZ and the HAZ.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To define the best quality of Ti-6Al-4V weld nugget strength, it is important to investigate the weld nugget’s physical and mechanical properties. The RSW parameters such as the welding current, time, and force are proved to be the most significant affected parameters to develop the weld nugget properties [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Similar materials with different thicknesses were previously studied [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%